A typology of gender-based needs - Rothermel, Ann-Kathrin; Nerino, Valentina; Zhang, Milin; Bias, Leandra; Amacker, Michèle (Frontiers in Political Science, 2025)
Feminism—both in its activist and theoretical form—arguably always focuses on exposing, challenging and re-thinking how gender is assumed, discussed and practiced. One key focus of feminists has been to show how gender—in the sense of assumptions and practices about masculinity and femininity—significantly influences the needs and demands of people and how they—in turn—are responded to (or not) across different political and societal regimes. However, to date there is no clear definition of what characterizes what we term “gender-based needs,” which could help us understand where, how, and why issues become salient as gendered. In fact, feminist academic discussions of gender-based needs, while often based on deep empirical engagements and contemporary events, rarely reach across policy areas or theoretical perspectives. In this article, we outline the results of an in-depth mixed-method literature review of 404 academic publications from different theoretical and empirical traditions across six European epistemic communities divided by language and geographical perspectives. Through this analysis, we derive a typology of how gender-based needs have been theorized across six dimensions of (1) gender lens, (2) policy field, (3) suggested solutions, (4) epistemological approach, (5) key actors, and (6) interest. By focusing on co-occurrences of these dimensions across the literature, we identify central elements as well as a variety of ideal types of gender-based needs, which are highlighted in the academic literature. Our typology provides an evidence-based conceptualization of gender-based needs, which can help to analyze and systematize geographical and epistemic patterns of how gender factors into political needs and demands. Moreover, the typology can serve as tool for policymakers to understand which gender-based needs are currently centered, and which neglected, in policymaking and practice.